A review on intelligent reflecting surface-based terahertz communication - Patel, Arpita; Shukla, Aasheesh (Institute of Advanced Engineering and Science, 2022)
Terahertz (THz)-band communications can be considered as the new frontline for future-generation wireless communication systems as it has a wider bandwidth in comparison to microwave and mmwave communications. It also promises to integrate the wide range of diverse applications. Because of high path loss and narrow spreading of THz waves, the transmission is extremely sensitive and signal coverage is a critical problem. To overcome this, an intelligent reflecting surface (IRS), has received great interest which steers the beams of THz waves by regulating the phase shifts to alleviate blockage and improve the coverage capability. In this paper, the role of IRS in conjunction with the THz communication has been discussed. Further, challenges and research directions of IRS for terahertz communication are also discussed.